2010
DOI: 10.1158/1535-7163.mct-09-1159
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent Induction of G1 Arrest and p21WAF1/CIP1 Expression by Ascofuranone, an Isoprenoid Antibiotic, through Downregulation of c-Myc

Abstract: Ascofuranone has been shown to have antitumor activity, but the precise molecular mechanism by which it inhibits the proliferation of cancer cells remains unclear. Here, we study the effects of ascofuranone on cell cycle progression in human cancer cells and find that ascofuranone induces G 1 arrest without cytoxicity with upregulation of p53 and p21 WAF1/CIP1 while downregulating c-Myc and G 1 cyclins. Chromatin immunoprecipitation assay and RNA interference studies with cells deficient in p53 and p21 show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…HCT-116 p53 -/-and HCT-116 p21 -/-cells lost both the growth-inhibitory effect and G 0 /G 1 arrest pattern of the cell cycle after DPD treatment. Previous studies have also shown the p21 induction and G 1 arrest by a p53-independent pathway (22) and the p21 involvement in cell growth and cell cycle of HCT-116 cells (23)(24)(25). It has been suggested that DPD induces p21 expression through a p53-independent pathway in colon cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…HCT-116 p53 -/-and HCT-116 p21 -/-cells lost both the growth-inhibitory effect and G 0 /G 1 arrest pattern of the cell cycle after DPD treatment. Previous studies have also shown the p21 induction and G 1 arrest by a p53-independent pathway (22) and the p21 involvement in cell growth and cell cycle of HCT-116 cells (23)(24)(25). It has been suggested that DPD induces p21 expression through a p53-independent pathway in colon cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…This suggests that both p53-dependent and p53-independent mechanisms may be involved in the up-regulation of Noxa and p21 induced by bortezomib in TRAF3-deficient malignant B cells. Indeed, multiple p53-independent mechanisms of Noxa and p21 induction have been described in the literature, including those dependent on Myc, RelA, p73, or E2F1 [3842]. Regardless of the detailed mechanisms, the functional consequences of Noxa and p21 up-regulation are clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p53-independent upregulation of p21 is facilitated by Chk-2 or by downregulation of c-myc (Aliouat-Denis et al 2005;Jeong et al 2010). Russo et al describe that diethylmaleate, an oxidizing agent, can activate p21 in p53-mutated conditions and block the cell cycle in G 1 phase (Russo et al 1995).…”
Section: Discussionmentioning
confidence: 99%